Methodologies and Challenges for Assessing Socio-Environmental Vulnerability in Urban Communities - Meneses, Fernanda Alves Gois; Costa, Jailton de Jesus; Araújo, Rozana Rivas de; Jesus , Robson Andrade de; Andrade, Joyce Dalline Silva (Technical and Scientific Journal Green Cities, 2025)
Socio-environmental vulnerability in urban areas, especially in favelas and urban communities, is a topic of increasing relevance due to the precarious conditions of housing, infrastructure and basic services that characterize these areas. This article reviews and analyzes the main methodologies used to assess socio-environmental vulnerability in these communities, highlighting the most widely used indexes and indicators, their advantages and limitations, and how they can be applied to guide public policies and intervention strategies. The analysis covers both quantitative and qualitative approaches, emphasizing the need to adapt these methodologies to the specific context of each community in order to provide an accurate and targeted assessment. In addition, the article highlights that the combination of different methods is essential to provide a comprehensive and effective vision, capable of supporting actions that promote social inclusion, improve quality of life and reduce socio-environmental inequalities in these vulnerable communities.